EVALUASI TINGKAT KEPATUHAN WAJIB PAJAK UMKM DI KPP PRATAMA MAKASSAR BARAT - Lina Mariana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
The research aims to determine the level of UMKM Taxpayer compliance based on PP No. 23 of 2018 at KPP Pratama West Makassar. The type of research used is a qualitative approach, the researcher describes the results of interviews and analyzes the data. This research conducted in June to July 2019. The level of taxpayer compliance in paying UMKM taxes from year by year has decreased significantly after having increased from 2015 to 2016, and declined again when the government applied the PP No. 23 of 2018. The KPP Pratama West Makassar devision made a program to socialize the implementation of the latest Government Regulations by distributing brochures to each of the markets and shops. The socialization is needed to notify UMKMs of the implementation of the latest Government Regulation, PP No. 23 of 2018 where the regulation confirms the reduction in UMKM tax rates to 0.5%. It is doing to increase the awareness of taxpayers to follow the rules with their tax obligations.